Low occurrence of Pseudomonas aeruginosa in agricultural soils with and without organic amendment - Deredjian, Amélie; Colinon, Céline; Hien, Edmond; Brothier, Elisabeth; Youenou, Benjamin; Cournoyer, Benoit; Dequiedt, Samuel; Hartmann, Alain; Jolivet, Claudy; Houot, Sabine; Ranjard, Lionel; Saby, Nicolas P. A.; et al. (Frontiers in Cellular and Infection Microbiology, 2014)
The occurrence of Pseudomonas aeruginosa was monitored at a broad spatial scale in French agricultural soils, from various soil types and under various land uses to evaluate the ability of soil to be a natural habitat for that species. To appreciate the impact of agricultural practices on the potential dispersion of P. aeruginosa, we further investigated the impact of organic amendment at experimental sites in France and Burkina Faso. A real-time quantitative PCR (qPCR) approach was used to analyze a set of 380 samples selected within the French RMQS (‘Réseau de Mesures de la Qualité des Sols’) soil library. In parallel, a culture-dependent approach was tested on a subset of samples. The results showed that P. aeruginosa was very rarely detected suggesting a sporadic presence of this bacterium in soils from France and Burkina Faso, whatever the structural and physico-chemical characteristics or climate. When we analyzed the impact of organic amendment on the prevalence of P. aeruginosa, we found that even if it was detectable in various manures (at levels from 103 to 105 CFU or DNA targets (g drywt)-1 of sample), it was hardly ever detected in the corresponding soils, which raises questions about its survival. The only case reports were from a vineyard soil amended with a compost of mushroom manure in Burgundy, and a few samples from two fields amended with raw urban wastes in the sub-urban area of Ouagadougou, Burkina Faso. In these soils the levels of culturable cells were below 10 CFU (g drywt)-1.